Mutation Load and Rapid Adaptation Favor Outcrossing Over Self-Fertilization - Morran, Levi T. (2009)
The tendency of organisms to reproduce by cross-fertilization despite numerous disadvantages relative to self-fertilization is one of the oldest puzzles in evolutionary biology. For many species, the primary obstacle to the evolution of outcrossing is the cost of producing of males(1), individuals that do not directly contribute offspring and thus diminish the long-term reproductive output of a lineage. Self-fertilizing organisms do not incur the cost of males and therefore should possess at least a two-fold numerical advantage over most outcrossing organisms(2). Two competing explanations for the widespread prevalence of outcrossing in nature despite this inherent disadvantage are the avoidance of inbreeding depression generated by selfing(3–5) and the ability of outcrossing populations to more rapidly adapt to environmental change(1,6,7). Here we show that outcrossing is favored in populations of C. elegans subject to experimental evolution both under conditions of increased mutation rate and during adaptation to a novel environment. In general, fitness increased with increasing rates of outcrossing. Thus, each of the standard explanations for the maintenance of outcrossing are correct, and it is likely that outcrossing is the predominate mode of reproduction in most species because it is favored under ecological conditions that are ubiquitous in natural environments.